Multi-stage Dynamic Plan of Regional Integrated Energy System Considering Medium and Long-Term Carbon Emission Reduction Constraints - Xiaofei WANG; Hongbo REN; Qiong WU; Qifen LI (Zhongguo dianli)
On a long-term scale, internal technological innovation and external environmental impact make the operation scenario of an integrated energy system increasingly complex. Based on the economic optimal configuration of regional energy resources and carbon emission reduction requirements, this paper proposes a multi-stage dynamic planning model for integrated energy systems considering medium and long-term carbon emission reduction constraints. The model can preset flexible stage division rules and different carbon emission reduction modes, and the optimal equipment allocation scheme is obtained by using a mixed integer linear programming method with the objective of minimizing the overall regional energy supply cost in the planning cycle. At the same time, a learning curve model is introduced to predict the change trend of equipment cost during the planning cycle, and new carbon reduction means such as hydrogen energy and carbon sink are considered. The simulation results for typical cases show that the increase in the number of planning stages achieves more effective dynamic matching of supply and demand, and the system economy and emission reduction effect are effectively improved. At the same time, different carbon emission reduction constraint patterns will lead to different carbon emission paths, which need to consider regional carbon reduction targets for the reasonable setting of emission reduction constraints.